2019
DOI: 10.1038/s41598-019-48388-7
|View full text |Cite
|
Sign up to set email alerts
|

Inner retinal thinning as a biomarker for cognitive impairment in de novo Parkinson’s disease

Abstract: We investigated the association between retinal changes measured using optical coherence tomography (OCT) and diverse clinical grading scales in patients with Parkinson’s disease (PD). Seventy-four eyes of 74 patients with de novo PD and 53 eyes of age-matched control subjects were included. The thickness of the peripapillary retinal nerve fiber layer (pRNFL) and macular ganglion cell-inner plexiform layer (mGCIPL) were measured. We analyzed the correlations between the clinical PD gradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 46 publications
4
43
3
2
Order By: Relevance
“…However, the majority of previous OCT studies in PD failed to demonstrate statistically significant results or yielded contradictory findings regarding the link between retinal atrophy and motor disability or disease duration 22 . Given that macular GCIPL atrophy has been reported in de novo PD patients 23 and in prodromal phases of LBD 24 and the lack of its correlation with disease duration or motor manifestations, it may suggest that retinal injury is an early phenomenon of iPD. Nonetheless, the mechanisms mediating the initiation and progression of retinal thinning in iPD are unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the majority of previous OCT studies in PD failed to demonstrate statistically significant results or yielded contradictory findings regarding the link between retinal atrophy and motor disability or disease duration 22 . Given that macular GCIPL atrophy has been reported in de novo PD patients 23 and in prodromal phases of LBD 24 and the lack of its correlation with disease duration or motor manifestations, it may suggest that retinal injury is an early phenomenon of iPD. Nonetheless, the mechanisms mediating the initiation and progression of retinal thinning in iPD are unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Several cross‐sectional studies using OCT have demonstrated that, compared to age‐matched controls, PD patients have an atrophy of inner retina that seems to be associated with disease duration and motor disability 22 . More recent publications have shown that the thinning of macular GCIPL in PD is linked to cognitive impairment in de novo patients 23 and to the risk of dementia 18 . Interestingly, our group found that visual dysfunction in PD is selectively associated with the thinning of GCIPL in the 1‐ to 3‐mm diameter ring area around the fovea (parafoveal GCIPL), 20 an OCT feature that has also been identified in patients with idiopathic rapid eye movement sleep behavior disorder—the earliest (prodromal) phase of LBD 24 .…”
mentioning
confidence: 99%
“… 7 Noninvasive retinal imaging in neurodegenerative disorders, including Lafora disease, enables identification of early disease states and provides new opportunities to monitor disease progression. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive retinal imaging has been used to demonstrate retinal alterations in a number of neurodegenerative diseases. 7 , 8 , 9 , 10 , 11 Here we used spectral domain optical coherence tomography (SD-OCT) and adaptive optics scanning light ophthalmoscopy (AOSLO) in three genetically confirmed individuals with Lafora disease to look for similar retinal structural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Many blinding diseases target cellular populations in the retina, and in vivo imaging approaches in mice have been used to study optic nerve injury 1 , 3 , 4 , macular degeneration 13 , stroke 5 , glaucoma 2 , 6 , and uveitis 7 . Furthermore, many central nervous system neurodegenerative conditions manifest in the retina including Alzheimer's disease 39 , multiple sclerosis 40 , and Parkinson's disease 41 . Therefore, this readily accessible technique for in vivo imaging of the retina can be applied as a tool to study a broad set of neurodegenerative conditions.…”
Section: Discussionmentioning
confidence: 99%